2022
DOI: 10.37992/2022.1302.077
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence, variability and character association analysis in chickpea (Cicer arietinum L.) genotypes under normal and late sown conditions

Abstract: Forty five chickpea genotypes were evaluated under normal and late sown conditions during Rabi,2017-18 in the experimental field of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…High estimates of heritability of the traits under study could be due to the larger genetic variability of the genotypes. Saleem et al (2008), Durga et al (2007), Thapa et al (2022) and Arshad et al (2004) observed high heritability in chickpea for days to flowering, days to maturity, test weight and plant height. High values obtained for heritability and genotypic variation indicated the presence of additive genetic effects, because of which conventional selection methods can be practiced for developing superior varieties Noor et al (2003).…”
mentioning
confidence: 99%
“…High estimates of heritability of the traits under study could be due to the larger genetic variability of the genotypes. Saleem et al (2008), Durga et al (2007), Thapa et al (2022) and Arshad et al (2004) observed high heritability in chickpea for days to flowering, days to maturity, test weight and plant height. High values obtained for heritability and genotypic variation indicated the presence of additive genetic effects, because of which conventional selection methods can be practiced for developing superior varieties Noor et al (2003).…”
mentioning
confidence: 99%